2020
DOI: 10.1080/02699931.2019.1710110
|View full text |Cite
|
Sign up to set email alerts
|

Affect enhances object-background associations: evidence from behaviour and mathematical modelling

Abstract: In recognition memory paradigms, emotional details are often recognized better than neutral ones, but at the cost of memory for peripheral details. We previously provided evidence that, when peripheral details must be recalled using central details as cues, peripheral details from emotional scenes are at least as likely to be recalled as those from neutral scenes. Here we replicated and explicated this result by implementing a mathematical modeling approach to disambiguate the influence of target type, scene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Here, we did observe a relative impairment for associative memory for negative emotion (as compared to neutral), replicating numerous prior findings using unrelated pairs (Touryan et al, 2007;Zimmerman & Kelley, 2010;Madan et al, , 2017Bisby & Burgess, 2014). It is worth noting, however, that some emotional associative memory studies have instead found enhancements due to emotion (e.g., Mickley Steinmetz et Affective bleed and memory precision 20 Madan et al, 2020). So far, the critical factor appears to be the presence of preexisting conceptual or semantic relationships (Madan et al, 2020;Barnacle et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Here, we did observe a relative impairment for associative memory for negative emotion (as compared to neutral), replicating numerous prior findings using unrelated pairs (Touryan et al, 2007;Zimmerman & Kelley, 2010;Madan et al, , 2017Bisby & Burgess, 2014). It is worth noting, however, that some emotional associative memory studies have instead found enhancements due to emotion (e.g., Mickley Steinmetz et Affective bleed and memory precision 20 Madan et al, 2020). So far, the critical factor appears to be the presence of preexisting conceptual or semantic relationships (Madan et al, 2020;Barnacle et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…For example, in a recent study by Montchal and colleagues (2019), temporal precision (measured using a task that inspired ours) was associated with functional MRI activity in hippocampal subregions and lateral entorhinal cortex. Yet our finding suggests that emotion does not impair all aspects of hippocampal binding, and indeed, there is good reason to believe that item-context bindings involve different mechanisms depending on the nature of the context (e.g., Dimsdale-Zucker et al, 2018;Madan et al, 2020). Follow-up neuroimaging work probing emotional effects on temporal memory (with aligned psychometrics) is needed to further explicate how these structures may contribute to the unexpected pattern of temporal behavioral effects observed in the present study versus their contribution to the "what" and "which" aspects of emotional memory.…”
Section: Discussionmentioning
confidence: 62%
“…That is, perhaps the timing was encoded as an intrinsic feature of an image (Mather, 2007). By analogy, a number of studies on emotion and memory show that properties in other domains that are intrinsic to a stimulus benefit from emotion, including stimulus color (MacKay et al, 2004), the visuospatial location of the stimulus (Costanzi et al, 2019; González-Garrido et al, 2015; Mather & Nesmith, 2008), and even objects overlaid on neutral background scenes (Madan et al, 2020). Critically, we note that in our study, negative emotion did not affect precision per se, but it did affect participants’ responding; in the neutral condition, there was a shift to later temporal estimates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a recent study by Montchal and colleagues (2019), temporal precision (measured using a task that inspired ours) was associated with fMRI activity in hippocampal subregions and lateral entorhinal cortex. Yet, our finding suggests that emotion does not impair all aspects of hippocampal binding and indeed, there is good reason to believe that item-context bindings involve different mechanisms depending on the nature of the context (e.g., Dimsdale-Zucker et al, 2017;Madan et al, 2020). Follow-up neuroimaging work probing emotional effects on temporal memory (with aligned psychometrics) is needed to further explicate how these structures may contribute to the unexpected pattern of temporal behavioral effects observed in the present study versus their contribution to the what and which aspects of emotional memory.…”
Section: Discussionmentioning
confidence: 62%
“…That is, perhaps the timing was encoded as an intrinsic feature of an image (Mather, 2007). By analogy, a number of studies on emotion and memory show that properties in other domains that are intrinsic to a stimulus benefit from emotion, including stimulus color (MacKay et al, 2004) the visuo-spatial location of the stimulus (Costanzi et al, 2019;Gonzalez-Garrido et al, 2015;Mather & Nesmith, 2008), and even objects overlaid on neutral background scenes (Madan et al, 2020). Critically, we note that in our study, negative emotion did not affect precision per se, but did affect participant's responding, such that for the neutral condition, there was a shift to later temporal estimates.…”
Section: Discussionmentioning
confidence: 99%